Secular trends in self reported sexual activity and satisfaction in Swedish 70 year olds: cross sectional survey of four populations, 1971-2001 - Beckman, Nils (BMJ Publishing Group Ltd., 2008)
Objective To study secular trends in self reported sexual behaviour among 70 year olds. Design Cross sectional survey. Settings Four samples representative of the general population in Gothenburg, Sweden. Participants 1506 adults (946 women, 560 men) examined in 1971-2, 1976-7, 1992-3, and 2000-1. Main outcome measures Sexual intercourse, attitudes to sexuality in later life, sexual dysfunctions, and marital satisfaction. Results From 1971 to 2000 the proportion of 70 year olds reporting sexual intercourse increased among all groups: married men from 52% to 68% (P=0.002), married women from 38% to 56% (P=0.001), unmarried men from 30% to 54% (P=0.016), and unmarried women from 0.8% to 12% (P<0.001). Men and women from later birth cohorts reported higher satisfaction with sexuality, fewer sexual dysfunctions, and more positive attitudes to sexuality in later life than those from earlier birth cohorts. A larger proportion of men (57% v 40%, P<0.001) and women (52% v 35%, P<0.001) reported very happy relationships in 2000-1 compared with those in 1971-2. Sexual debut before age 20 increased in both sexes: in men from 52% to 77% (P<0.001) and in women from 19% to 64% (P<0.001). Conclusion Self reported quantity and quality of sexual experiences among Swedish 70 year olds has improved over a 30 year period.